Case Report: A Novel AChR Epsilon Variant Causing a Clinically Discordant Salbutamol Responsive Congenital Myasthenic Syndrome in Two Egyptian Siblings - Gómez-García de la Banda, Marta; Simental-Aldaba, Emmanuel; Fahmy, Nagia; Sternberg, Damien; Blondy, Patricia; Quijano-Roy, Susana; Malfatti, Edoardo (Frontiers in Neurology, 2022)
Congenital myasthenic syndromes (CMS) are inherited disorders that lead to abnormal neuromuscular transmission. Post-synaptic mutations are the main cause of CMS, particularly mutations in CHRNE. We report a novel homozygous CHRNE pathogenic variant in two Egyptian siblings showing a CMS. Interestingly, they showed different degree of extraocular and skeletal muscle involvement; both presented only a partial response to cholinesterase inhibitors, and rapidly and substantially ameliorated after the addition of oral β2 adrenergic agonists. Here, we enlarge the genetic spectrum of CHRNE-related congenital myasthenic syndromes and highlight the importance of a β2 adrenergic agonists treatment.